Toxoplasmosis seroepidemiology in pregnant women in a city in the Northwest region of the Paraná State, Brazil - Caetano, Isabel Cristina da Silva; Rodrigues, Graziela Vendrame; Gonçalves, Daniela Dib; Lopes-Mori, Fabiana Maria Ruíz; Mitsuka-Breganó, Regina; Freire, Roberta Lemos; Navarro, Italmar Teodorico; Matumoto, Francisco Hiroshi; Dias Neto, José Gonçalves; Merlini, Luiz Sergio (Medicina Veterinária, 2017)
Toxoplasmosis is a zoonosis caused by the Toxoplasma gondii protozoa. The congenital form happens when the parasite reaches the fetus through the placenta and causes damages of different intensities, which can be consequence of the strain virulence, of the immune response capability of the pregnant woman or even of the pregnancy stage, and can result in fetal death or severe clinical symptomatology. The aim of this paper was to determine the prevalence of antibodies to Toxoplasma gondii antibodies in pregnant woman seen at the Basic Health Units (BHU) in the city of Umuarama (PR) and check for possible toxoplasmosis associations with social-demographic characteristics, behavior and environmental variables. In this study, a total of 813 pregnant women who had their prenatal exams at the BHU in the city of Umuarama (PR) were included. Blood samples collected from these subjects were submitted to IgG and IgM anti-T. gondii antibody survey. Each pregnant woman answered an epidemiological questionnaire for the detection of variables, which were later analyzed by the EpiInfo program. The prevalence detected for IgG and IgM anti-T. gondii antibodies were 56.8% and 1.0%, respectively. The variables age group, education level, per capita income, number of pregnancies, ingestion of fresh sausage, presence of peridomiciliary cats in the backyard and the habit of ingesting farm milk showed association to the infection by T. gondii.